PENGARUH BEBAN BAGI HASIL DAN FEE-BASED INCOME TERHADAP LABA BANK JABAR BANTEN SYARIAH - Sifaur Rohmah; Sukron Mamun; Matnin (Jurnal Ekonomi Syariah Pelita Bangsa, 2022)
This research is a quantitative approach. This study uses the monthly financial statement population of Bank Jabar Banten Syariah for the period 2018-2020. While the data collection techniques in this study with documentation. The data analysis used is the classical assumption test, multiple linear regression analysis, hypothesis testing and the coefficient of determination (R2) test. The variables used in this study are the amount of Profit Sharing Expenses, the amount of Fee-Based Income and the amount of Bank Profit. From the results of the t test, it was obtained that X1 had a sig value of 0.020<0.05 and a tcount of 2.449>2.035, while X2 had a sig value of 0.248>0.05 and a tcount of 1.176<2.035. As for the F test, it is known that the sig X1 and X2 values simultaneously are 0.00 <0.05 and the Fcount value is 20.305> 3.28. And based on the coefficient of determination test (R2) the values of X1 and X2 have a contribution percentage of 55.2% to the Bank's Profit and the remaining 44.8% is influenced by other variables not included in this study.